2014
DOI: 10.2217/crc.14.34
|View full text |Cite|
|
Sign up to set email alerts
|

VATE: VAlidation of high TEchnology based on large database analysis by learning machine

Abstract: SummaryThe interaction between implementation of new technologies and different outcomes can allow a broad range of researches to be expanded. The purpose of this paper is to introduce the VAlidation of high TEchnology based on large database analysis by learning machine (VATE) project that aims to combine new technologies with outcomes related to rectal cancer in terms of tumor control and normal tissue sparing. Using automated computer bots and the knowledge for screening data it is possible to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…We would advise to validate prediction models on trial and routine clinical cohorts as also suggested by Booth and Tannock and proposed in the VATE project . The quality of cohorts from clinical trials are needed to identify which variables need to be reported in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…We would advise to validate prediction models on trial and routine clinical cohorts as also suggested by Booth and Tannock and proposed in the VATE project . The quality of cohorts from clinical trials are needed to identify which variables need to be reported in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, more advanced technologies have been adopted in clinical use in the last decade, such as image guided radiation therapy, different advanced dose modulation and delivery techniques, particle therapy, with a increasing attention to address resources in a reliable and cost-effective technologies [4]. Furthermore, radiotherapy is actually more a biological intervention rather than a physical, because of its effects on cellular and molecular level [7][8]; the heterogeneity of dose distribution in the irradiated and normal tissue should be considered [1]. In the past, in order to analyse the treatment effects in radiation oncology, several models were elaborated, to show the correlation between radiotherapy dose and outcomes, through different dose-reduction methods; the probit-based one (or the Lyman--Kutcher-Burman model) [9] and the logit-based one [10] are the most used dose-response models.…”
Section: Perspectivesmentioning
confidence: 99%
“…Collecting data, without knowing beforehand what the relevant features will be, implies a standardization of any variable to collect to universally define data and procedures allowing automatic and consistent upload from any data sources [1]. This process will take advantage of an ontology definition to describe data, both for being sure to share the same meanings between researchers and to allow automatic inference/reasoning from computers.…”
Section: Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations